Complex genotype–phenotype correlation of MYH11: new insights from monozygotic twins with highly variable expressivity and outcomes - Xiaojiao Wei; Yunting Ma; Bobo Xie; Chunrong Gui; Meizhen Shi; Xianda Wei; Yan Huang; Xin Fan; Qiaozhen Wei; Qingmei Huang; Li Deng; Chi Zhang; et al. (BMC Medical Genomics, 2024)
Abstract Background Thoracic aortic aneurysm/dissection (TAAD) and patent ductus arteriosus (PDA) are serious autosomal-dominant diseases affecting the cardiovascular system. They are mainly caused by variants in the MYH11 gene, which encodes the heavy chain of myosin 11. The aim of this study was to evaluate the genotype–phenotype correlation of MYH11 from a distinctive perspective based on a pair of monozygotic twins. Methods The detailed phenotypic characteristics of the monozygotic twins from the early fetal stage to the infancy stage were traced and compared with each other and with those of previously documented cases. Whole-exome and Sanger sequencing techniques were used to identify and validate the candidate variants, facilitating the analysis of the genotype–phenotype correlation of MYH11. Results The monozygotic twins were premature and presented with PDA, pulmonary hypoplasia, and pulmonary hypertension. The proband developed heart and brain abnormalities during the fetal stage and died at 18 days after birth, whereas his sibling was discharged after being cured and developed normally post follow-up. A novel variant c.766 A > G p. (Ile256Val) in MYH11 (NM_002474.2) was identified in the monozygotic twins and classified as a likely pathogenic variant according to the American College of Medical Genetics/Association for Molecular Pathology guidelines. Reviewing the reported cases (n = 102) showed that the penetrance of MYH11 was 82.35%, and the most common feature was TAAD (41.18%), followed by PDA (22.55%), compound TAAD and PDA (9.80%), and other vascular abnormalities (8.82%). The constituent ratios of null variants among the cases with TAAD (8.60%), PDA (43.8%), or compound TAAD and PDA (28.6%) were significantly different (P = 0.01). Further pairwise comparison of the ratios among these groups showed that there were significant differences between the TAAD and PDA groups (P = 0.006). Conclusion This study expands the mutational spectrum of MYH11 and provides new insights into the genotype–phenotype correlation of MYH11 based on the monozygotic twins with variable clinical features and outcomes, indicating that cryptic modifiers and complex mechanisms beside the genetic variants may be involved in the condition.